The impact of using celebrity endorsers on the brand equity of luxury companies - Carmo, Filipa de Oliveira Ribeiro Infante do (2021)
Drawing from the brand equity model of Aaker, the aim of this dissertation is to understand how the use of celebrity endorsers as a communication strategy affects luxury brands’ equity. I used a qualitative approach and conducted 39 in-depth interviews with participants from generation Y. The findings of this research show that the use of celebrity endorsers affects the brand equity of luxury brands through two dimensions: brand loyalty and brand associations. The dimension of perceived quality revealed an ambiguous influence, while brand awareness is not a channel through which the use of celebrity endorsers affects the brand equity of luxury brands